ANTESEDEN PEMBELIAN PRODUK HIJAU - Dita Kameilinda Junaedi; Indah Fatmawati (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2016)
This research aims to analyze the influence of environmental consciousness towards a green purchasing decision. In this research environmental consciousness covers of environment knowledge, environment attitude and green behavior which is recycled behavior. The sample in this research that is consumers of the green product. The samples are 113 respondents chosen by using purposive sampling. Multiple regression analyzers were applied in analyzing the data. The analysis results showed that environment knowledge and attitude of customer have significant influence. Management needs to improve the initiation of green programs with market education to increase the environment knowledge and attitude of customers.Keywords: Environmental Consciousness; Green Product; Environment Knowledge; Environment Attitude; Recycle Behavior and Green Purchasing Decision.